Kierkegaard's Journals and Notebooks, Volume 5 : Journals NB6-NB10 - Kierkegaard, Soren, 1813-1855 (Book collections on Project MUSE., 2011)
For over a century, the Danish thinker Soren Kierkegaard (1813-55) has been at the center of a number of important discussions, concerning not only philosophy and theology, but also, more recently, fields such as social thought, psychology, and contemporary aesthetics, especially literary theory. Despite his relatively short life, Kierkegaard was an extraordinarily prolific writer, as attested to by the 26-volume Princeton University Press edition of all of his published writings.